M-Net based stacked autoencoder for ransomware detection using blockchain data - Nathan, Uma Devi Gurumuni; Vadivu, P. Balashanmuga; Maram, Balajee; Gopisetty, Guru Kesava Dasu; Das, Smritilekha; T, Daniya (Applied soft computing, 2024)
Ransomware is a kind of malevolent program software that encrypts the items on the hard disc and prevents the clients from accessing them until they are paid a ransom. Associations like monetary establishments and medical care areas (i.e., smart medical care) are mostly targeted by ransomware attacks. Ransomware assaults are crucial holes still in blockchain technology and prevent effective data communication in networks. This study aims to introduce an efficient system, named M-Net-based Stacked Autoencoder (M-Net_SA) for ransomware detection using blockchain data. Initially, the input data is taken from a dataset and then sent to the feature extraction process, which utilizes sequence-based statistical features. After that, data transformation is completed using the Yeo-Johnson transformation to transform the data into a usable format. After that, feature fusion is executed using a Deep Q-network (DQN) with Lorentzian similarity to enhance the representativeness of the target features. Finally, ransomware detection is accomplished by the proposed M-Net_SA, which is the integration of MobileNet and Deep Stacked Autoencoder (DSAE). The experimental validation of the proposed M-Net_SA is compared with other conventional techniques and the proposed model attained maximum accuracy, sensitivity, and specificity of 0.959, 0.967, and 0.957 respectively. •Data transformation is processed utilizing the Yeo-Johnson transformation.•Feature fusion is executed using a Deep Q-network.•Ransomware detection is effectuated using the M-Net-based Stacked Autoencoder.